Diagnostic capabilities of cardiac computed tomography in the preoperative diagnosis of hypertrophic cardiomyopathy - Olga Y. Dariy; Liudmila A. Yurpolskaya; Inna E. Rychina; Aleksey V. Dorofeev; Elena Z. Golukhova (Digital Diagnostics)
BACKGROUND: A comprehensive approach to studying hypertrophic cardiomyopathy with diagnostic equipment and the latest scanning methods will ensure quality control and effective treatment of patients with this condition. The implementation of innovative technologies and computer calculation using next-generation scanners may become relevant and promising in studying various phenotypes of left ventricular remodeling in combination with abnormalities of the chordopapillary apparatus of the mitral valve and myocardial structure.